On Some Differential Features of Word Creation - Kovačević, Borko N. (Collection of Papers of the Faculty of Philosophy in Priština, 2023)
This paper dicsusses some features of word creation that this type of lexicogenesis differentiate from word formation (as lexicogenesis by typical morphological processes). The word creation processes that have been analyzed are blending, clipping, and acronimization. As the differential features of these processes, creation (inventivenes), intentionality, and (semantic) nontransperancy, as well as form reduction are presented. The conclusion is that in the case of the opposition between word creation and word formation, it is better to talk about prototypical categories. In this context, creation (inventivenes), intentionality, (semantic) nontransperancy, and form reduction are considered as prototypical features of the word creation processes.